PENGARUH LAMA PERENDAMAN DAN PEREBUSAN TERHADAP RESIDU INSEKTISIDA BERBAHAN AKTIF KLORPIRIFOS DAN NILAI NUTRISI KACANG PANJANG (Vigna sinensis) - Bayu Chandraliawathy, R. Ag. Ay. Ag.; Lani Triani, I. G. A.; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September, 2016)
The aims of the research were to determine the effect of soaking  and boiling time on the chlorpyrifos  residu level  and the nutrition value,  especially Vitamin C and crude fiber of long bean (Vigna sinensis). The other objective of the research was to find out the right soaking and boiling time to reduce chlorpyrifos  residu and produce the good nutrition  of long bean. The randomized block design was used in the experiment which the factorial pattern of the experiment was done with two factors, namely soaking time and boiling time. The result showed that the interaction treatment of soaking and boiling time influenced the chlorpyrifos  residu  and the nutrition value of long bean. The soaking time for 10 minutes and boiling time for 5 minutes could decrease the  level of chlorpyrifos to 0,0427 ppm  from  0,2364 ppm  of fresh  long bean. The vitamin C and crude fiber  content of the long bean were 41,72 mg/g and 1,55% respectively. The color, texture, and the taste of the long bean were dark green, soft, and the panelist were still like the product. Keywords: chlorpyrifos residu, long beans, soaking, boiling, vitamin C, and crude fiber.
Keywords: 102